Increased expression of Triad1 is associated with neuronal apoptosis after intracerebral hemorrhage in adult rats. (2nd August 2020) - Wang, Shuyao; Xue, Feng; Li, Wanyan; Shan, Yisi; Gu, Xingxing; Shen, Jiabing; Ke, Kaifu
Abstract: Objective: It has been demonstrated that Triad1 (2 RING fingers and double RING finger linked 1) negatively regulates myeloid cell growth and induces cell apoptosis. However, its functions in intracerebral hemorrhage (ICH) disease have not been conducted. In this study, the role of Triad1 in rat model of ICH was explored. Methods: We observe an increasing expression of Triad1 in areas adjacent to hematoma after ICH. Immunofluorescence shows that Triad1 is colocalized with neurons, while not microglia or astrocyte, indicates its correlation with neuronal activities following ICH. Results: As neuronal apoptosis is the most crucial event in ICH disease, the expression of active caspase-3 and p53 is also enhanced around the hematoma, which is consistent with Triad1 in expression tendency. In turn, Triad1 depletion in primary cortical neurons decreased the apoptosis of neurons after using Triad1 shRNA. Conclusion: We conclude that inhibition of Triad1 expression might protect the brain from secondary damage following ICH.